Tiktok Sebagai Sarana Promosi Program Kampus Merdeka - Agnela, Teresia; Yoedtadi, Moehammad Gafar (Prologia, 2023)
The Directorate General of Higher Education has a program to invite students to get hands-on experience in the field in the Merdeka Learning Campus Merdeka program. The Directorate General of Higher Education utilizes social media to disseminate the program. From this social media, it is hoped that the public will understand the meaning of Freedom to Learn on an Independent Campus, and students will welcome this program. In addition, it is hoped that students will be interested in participating actively in the programs offered by universities. One of the social media used is TikTok, which has experienced rapid development in the last 2 years. The audience for TikTok is mostly young people. This study aims to determine the strategy of the social media division at the Directorate General of Higher Education in informing the Merdeka Learning Campus Merdeka program by using social media TikTok. This research uses a qualitative approach with a case study method. Data collection is done by interviews, observation and documentation. Research informants are social media coordinators, content creators and the target audience for TikTok, Directorate General of Higher Education. The results of the study show that the strategy owned by the Directorate General of Higher Education is actually in accordance with the POST (People-Objectives-Strategy-Technology) method of social media planning, but for now the Directorate General of Higher Education is still more concerned with quantity than content quality. Direktorat Jendral Pendidikan Tinggi memiliki program untuk mengajak mahasiswa mendapat pengalaman langsung terjun ke lapangan dalam program Merdeka Belajar Kampus Merdeka. Ditjen Dikti memanfaatkan media sosial untuk menyebarluaskan program tersebut. Dari media sosial ini diharapkan masyarakat memahami makna Merdeka Belajar Kampus Merdeka, dan mahasiswa menyambut baik program ini. Di samping itu diharapkan mahasiswa tertarik untuk ikut serta secara aktif pada program-program yang ditawarkan oleh perguruan tinggi. Media sosial yang digunakan salah satunya adalah TikTok yang mengalami perkembangan pesat 2 tahun belakangan ini. Khalayak TikTok sebagian besar adalah anak muda. Penelitian ini bertujuan untuk mengetahui strategi divisi media sosial pada Ditjen Dikti dalam menginformasikan program Merdeka Belajar Kampus Merdeka dengan menggunakan media sosial TikTok. Penelitian ini dilakukan dengan menggunakan pendekatan kualitatif dengan metode studi kasus. Pengumpulan data dilakukan dengan wawancara, observasi dan dokumentasi. Informan penelitian adalah koordinator media sosial, pembuat konten dan target khalayak TikTok Ditjen Dikti. Hasil penelitian memperoleh hasil bahwa strategi yang dimiliki oleh Ditjen Dikti sebenarnya sudah sesuai dengan perencanaan media sosial metode POST (People-Objectives-Strategy-Technology), akan tetapi untuk saat ini Ditjen Dikti masih lebih mementingkan kuantitas dibandingkan kualitas konten.